Pinning down the social license to operate (SLO): The problem of normative complexity. (December 2018) - Brueckner, Martin; Eabrasu, Marian
Abstract: The 'social license to operate' (SLO) concept, whilst ubiquitous in industry and academia, to this day, continues to defy clear definition. This ambiguity encourages the proliferation of conflicting claims to such a license and complicates the assessment of their legitimacy. Observing that a dimension of SLO's ambiguity is normative, this paper seeks to explore this normativity aspect further, with a view to discerning the disagreements on what makes an SLO legitimate and what delegitimizes it. The legitimacy gap in SLO discussions is illustrated in light of a case study from the Australian minerals and energy sector and explained in the context of the normative complexity surrounding the SLO construct, which seems to limit the transferability of findings from the growing number of SLO studies. As possible means for addressing this normative complexity the conceptual widening, approximation and standardization of the SLO are proposed in an attempt to overcome the stalemate resulting from competing social license claims and social license interpretations. Highlights: The social license to operate concept defies clear definition, complicating the legitimacy assessment of conflicting social license claims. This paper addresses the legitimacy gap in social licensing and highlights the normative complexity surrounding the social license construct. The conceptual widening, approximation and standardization of the social license are proposed as means of addressing its normative complexity.